Does a happy destination bring you happiness? Evidence from Swiss inbound tourism - Chen, Yong; Li, Xiang (Robert) (Tourism management (1982), 2018)
This study aims to explain tourist happiness by examining a specific destination in which happiness is generated for tourists via their travel behavior at the destination. Building upon the spillover theory of happiness, we developed a destination-based model of tourist happiness, which is shaped by destination image and service quality and mediated by tourist satisfaction and life satisfaction. This model was tested using data from 1048 inbound tourists in Switzerland in 2015. We found that destination image is positively associated with life satisfaction, eudaimonia, and positive and negative affect; no evidence indicated the effect of service quality on life satisfaction and negative affect. In particular, life satisfaction can largely predict eudaimonia and positive and negative affect. We also discovered that negative affect is poorly explained by its antecedents in the tourism context, suggesting that tourists are reluctant to link their travel experiences to negative affect. •A destination-based model of happiness is developed based on the spillover theory.•Destination image is associated with life satisfaction, eudaimonia, and affect.•Life satisfaction can predict eudaimonia and both positive and negative affect.•Tourists are reluctant to link their travel experience to negative affect.•Tourist satisfaction has strong mediating effects in the model of tourist happiness.